Solving train scheduling problems as a job shop: A brief review - Frank Werner (Annals of Mathematics and Physics - Peertechz Publications, 2022)
An interesting practical problem is the single-track train scheduling problem which can be considered a job shop scheduling problem, namely since the sequence of sections is fixed for a train route, it corresponds to fixed machine routes (technological orders) in a job shop scheduling problem. However, for a train scheduling problem, typically some additional constraints such as blocking, sidings, stations with parallel tracks, deadlocks, train length, or headways, etc. have to be considered. The job shop problem has been well investigated in the literature and belongs to the hardest problems in scheduling theory. In this mini-review, some results in this area are discussed, where the main focus is on results that the author has obtained with his collaborators and Ph.D. students during the last decade. MSC classification: 90 B 35